Solar influences on the Earth’s atmosphere: solved and unsolved questions - Georgieva, Katya; Veretenenko, Svetlana (Frontiers in Astronomy and Space Sciences, 2023)
The influence of the Sun on the Earth’s atmosphere and climate has been a matter of hot debate for more than two centuries. In spite of the correlations found between the sunspot numbers and various atmospheric parameters, the mechanisms for such influences are not quite clear yet. Though great progress has been recently made, a major problem remains: the correlations are not stable, they may strengthen, weaken, disappear, and even change sign depending on the time period. None of the proposed so far mechanisms explains this temporal variability. The basis of all solar activity is the solar magnetic field which cyclically oscillates between its two components—poloidal and toroidal. We first briefly describe the operation of the solar dynamo transforming the poloidal field into toroidal and back, the evaluated relative variations of these two components, and their geoeffective manifestations. We pay special attention to the reconstruction of the solar irradiance as the key natural driver of climate. We point at some problems in reconstructing the long-term irradiance variations and the implications of the different irradiance composite series on the estimation of the role of the Sun in climate change. We also comment on the recent recalibration of the sunspot number as the only instrumentally measured parameter before 1874, and therefore of crucial importance for reconstructing the solar irradiance variations and their role in climate change. We summarize the main proposed mechanisms of solar influences on the atmosphere, and list some of the modelling and experimental results either confirming or questioning them. Two irradiance-driven mechanisms have been proposed. The “bottom-up” mechanism is based on the enhanced absorption of solar irradiance by the oceans in relatively cloud-free equatorial and subtropical regions, amplified by changes in the temperature gradients, circulation, and cloudiness. The “top-down” mechanism involves absorption by the stratospheric ozone of solar UV radiation whose variability is much greater than that of the visible one, and changes of large-scale circulation patterns like the stratospheric polar vortex and the tropospheric North Atlantic Oscillation. The positive phase of the tropospheric North Atlantic Oscillation indicative of a strong vortex is found to lag by a couple of years the enhanced UV in Smax. It was however shown that this positive response is not due to lagged UV effects but instead to precipitating energetic particles which also peak a couple of years after Smax. The solar wind and its transients modulate the flux of galactic cosmic rays which are the main source of ionization of the Earth’s atmosphere below ∼50 km. This modulation leads to modulation of the production of aerosols which are cloud condensation nuclei, and to modulation of cloudiness. Increased cloudiness decreases the solar irradiance reaching the low atmosphere and the Earth’s surface. Variations of the galactic cosmic rays also lead to variations of the electric currents and the ionospheric potential in the polar caps which may intensify microphysical processes in clouds and thus also cause cloudiness variations. Solar energetic particles are produced during eruptive events at the Sun. They produce reactive odd hydrogen HOx and nitrogen NOx which catalytically destroy ozone in the mesosphere and upper stratosphere—“direct effect.” NOx which are long-lived in the lack of photoionization during the polar night, can descend to lower altitudes and destroy ozone there producing a delayed “indirect effect.” In the absence of sunlight ozone absorbs longwave outgoing radiation emitted by the Earth and atmosphere. Ozone depletion associated with ionization increases leads to cooling of the polar middle atmosphere, enhancing the temperature contrast between polar and midlatitudes and, thus, the strength of the stratospheric polar vortex. Solar energetic particles are powerful but sporadic and rare events. An additional source of energetic particles are the electrons trapped in the Earth’s magnetosphere which during geomagnetic disturbances are accelerated and precipitate into the atmosphere. They are less energetic but are always present. Their effects are the same as that of the solar energetic particles: additional production of reactive HOx and NOx which destroy ozone resulting in a stronger vortex and a positive phase of the North Atlantic Oscillation. It has been shown that the reversals of the correlations between solar activity and atmospheric parameters have a periodicity of ∼60 years and are related to the evolution of the main forms of large-scale atmospheric circulation whose occurrence has a similar periodicity. The large-scale circulation forms are in turn influenced by the state of the polar vortex which can affect the troposphere-stratosphere interaction via the propagation of planetary waves. Two solar activity agents are supposed to affect the stratospheric polar vortex: spectral solar irradiance through the “top-down” mechanism, and energetic particles. Increased UV irradiance was found to lead to a negative phase of the North Atlantic Oscillation, while increased energetic particles result in a positive phase. Solar irradiance, like sunspots, is related to the solar toroidal field, and energetic particle precipitation is related to the solar poloidal field. In the course of the solar cycle the irradiance is maximum in sunspot maximum, and particle precipitation peaks strongly in the cycle’s declining phase. The solar poloidal and toroidal fields are the two faces of the solar large-scale magnetic field. They are closely connected, but because they are generated in different domains and because of the randomness involved in the generation of the poloidal field from the toroidal field, on longer time-scales their variations differ. As a result, in some periods poloidal field-related solar drivers prevail, in other periods toroidal field-related drivers prevail. These periods vary cyclically. When the poloidal field-related drivers prevail, the stratospheric polar vortex is stronger, and the correlation between solar activity and atmospheric parameters is positive. When toroidal field-related drivers prevail, the vortex is weaker and the correlations are negative.